Input-Based Incremental Approach versus Image Schema Instruction for Improving Preparatory Schoolers' English as a Foreign Language Vocabulary Acquisition - محمد أبو المجد (Faculty of Education - Port Said University, 2023)
This research aimed to improve the EFL vocabulary acquisition among preparatory schoolers at public schools and to compare between Input-Based Incremental Approach (IBI) and Image Schema Instruction (ISI) for better EFL vocabulary acquisition. The research design was two group pre and post-test quasi-experimental design. The participants were divided into three groups of 33 1st year preparatory schoolers per class: IBI experimental group, ISI experimental group and control group. Two tools were developed, validated and implemented by the researcher: a vocabulary test to examine schoolers' vocabulary acquisition and three opinionnaires to elicit the three groups' opinions in terms of understanding, memorizing and practicing vocabulary for better acquisition. It was concluded that IBI and ISI had high positive effects on improving the participants' vocabulary acquisition when testing their effect sizes individually and with respect to the control group's conventional classroom vocabulary teaching practices. But when compared to each other in effect size, neither IBI nor ISI had a higher positive effect than the other due to the drawbacks of each pedagogy that could be substantially resolved if both pedagogies were used in combination or interchangeably. IBI and ISI were beneficial to improving the EFL vocabulary acquisition among the experimental participants for the special features and qualities provided by each of them for better vocabulary acquisition.